OPTICAL AND MAGNETIC PROPERTIES OF AlN/Mn ALTERNATING LAYERS - Roberto Bernal-Correa (Momento, 2011)
In this paper, we present a study of the optical and magnetic properties of AlN/Mn alternating layers, deposited on glass and Si (100) substrates by r.f. magnetron sputtering. The optical characterization was performed using micro-Raman in order to determine A1(TO) E1(TO) and E2(high) vibrational modes of AlN, and a local vibrational mode (MVL) of Mn. The magnetic behavior was analyzed by vibrating sample magnetometry (VSM). From temperature dependent magnetization at zero field cooling (ZFC) and field cooling (FC), and hysteresis loop measurements it was determinated that AlN/Mn multilayers show a ferromagnetic ordering.